Prenatal and adult androgen activities in alcohol dependence. (6th April 2017) - Lenz, B.; Mühle, C.; Braun, B.; Weinland, C.; Bouna‐Pyrrou, P.; Behrens, J.; Kubis, S.; Mikolaiczik, K.; Muschler, M.‐R.; Saigali, S.; Sibach, M.; Tanovska, P.; et al.
Abstract : Objective: Alcohol dependence is more prevalent in men than in women. The evidence for how prenatal and adult androgens influence alcohol dependence is limited. We investigated the effects of prenatal and adult androgen activity on alcohol dependence. Moreover, we studied how the behaviours of pregnant women affect their children's prenatal androgen load. Method: We quantified prenatal androgen markers (e.g., second‐to‐fourth finger length ratio [2D : 4D]) and blood androgens in 200 early‐abstinent alcohol‐dependent in‐patients and 240 controls (2013–2015, including a 12‐month follow‐up). We also surveyed 134 women during pregnancy (2005–2007) and measured the 2D : 4D of their children (2013–2016). Results: The prenatal androgen loads were higher in the male alcohol‐dependent patients compared to the controls (lower 2D : 4D, P =  0.004) and correlated positively with the patients' liver transaminase activities ( P  <   0.001) and alcohol withdrawal severity ( P  =   0.019). Higher prenatal androgen loads and increasing androgen levels during withdrawal predicted earlier and more frequent 12‐month hospital readmission in alcohol‐dependent patients ( P  <   0.005). Moreover, stress levels ( P =  0.002), alcohol ( P =  0.010) and tobacco consumption ( P =  0.017), and lifetime stressors ( P =  0.019) of women during pregnancy related positively to their children's prenatal androgen loads (lower 2D : 4D). Conclusion: Androgen activities in alcohol‐dependent patients and behaviours of pregnant women represent novel preventive and therapeutic targets of alcohol dependence.